2018
DOI: 10.1002/ecs2.2176
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the establishment and growth of tree seedlings at Subarctic alpine treelines

Abstract: Citation: Kambo, D., and R. K. Danby. 2018. Factors influencing the establishment and growth of tree seedlings at Subarctic alpine treelines. Ecosphere 9(4):e02176. 10.1002/ecs2.2176Abstract. Significant treeline advance can only occur with successful establishment, growth, and survival of new seedlings. Several studies have examined microsite factors at single locations to explain the presence/ absence of seedlings at treeline. We conducted a much larger observational study and included multiple factors to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 86 publications
(106 reference statements)
0
23
0
Order By: Relevance
“…Second (Case B), despite the very limited geographical extent of the study area (200 m × 600 m), it displayed variation in wind exposure, temperature, soil depth, and moisture due to its location on and along a small ridge with variations in aspect. As discussed by Kambo and Danby [63], these are all factors influencing seedling establishment, growth, and mortality in tree line environments, and aspect-related differences have been established in the literature in multiple forest, tree line, and tundra sites [63]. Thus, we divided the area into four sub-regions (see Figure 6A) according to aspect, slope, elevation, and soil depth (occurrence of bedrock outcrops).…”
Section: Discussionmentioning
confidence: 99%
“…Second (Case B), despite the very limited geographical extent of the study area (200 m × 600 m), it displayed variation in wind exposure, temperature, soil depth, and moisture due to its location on and along a small ridge with variations in aspect. As discussed by Kambo and Danby [63], these are all factors influencing seedling establishment, growth, and mortality in tree line environments, and aspect-related differences have been established in the literature in multiple forest, tree line, and tundra sites [63]. Thus, we divided the area into four sub-regions (see Figure 6A) according to aspect, slope, elevation, and soil depth (occurrence of bedrock outcrops).…”
Section: Discussionmentioning
confidence: 99%
“…We observed apical death and in some cases resprouting of many seedlings at the treeline site. Wind damage and desiccation is an important determinant of tree seedling success at other treeline locations [64,65].…”
Section: Plos Onementioning
confidence: 99%
“…Ultimately having multi-temporal acquisitions of ALS data at treeline ecotones could allow for a more informed assessment of the vertical forest structure (e.g., Nelson 2007, Hauglin et al 2018). Kambo and Danby (2018), working in sub-arctic treelines in the Yukon, explored the drivers of tree seedling establishment at alpine treelines. The authors found that the occurrence of tree seedlings across 640 sites was best explained by the proximity, height, and upslope orientation of shrubs.…”
Section: Structure Classmentioning
confidence: 99%